Advances in Production Management Systems. Artificial Intelligence for Sustainable and Resilient Production Systems: IFIP WG 5. 7 International Conference, APMS 2021, Nantes, France, September 5-9, 2021, Proceedings, Part V - Dolgui, Alexandre; Bernard, Alain; Lemoine, David; von Cieminski, Gregor; Romero, David (Springer International Publishing AG, 2021)
The five-volume set IFIP AICT 630, 631, 632, 633, and 634 constitutes the refereed proceedings of the International IFIP WG 5.7 Conference on Advances in Production Management Systems, APMS 2021, held in Nantes, France, in September 2021.* The 378 papers presented were carefully reviewed and selected from 529 submissions.